Survey of Knowledge, Attitudes, and Behaviors Related to Monkeypox Among Men Who Have Sex with Men (MSM) In Kendari City In 2024 - Hariati Lestari (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Monkeypox, also known as monkey pox, is a zoonotic disease caused by the Orthopoxvirus from the Poxviridae family. The virus was first identified in a sick monkey in Denmark in 1958 after being transported from Singapore. The first human case was detected in a child in the Democratic Republic of the Congo in 1970. The transmission of this virus, which can spread both between humans and from animals to humans, has led to changes in health policies and travel procedures, ultimately affecting social interactions, trade, and culture. Objectives: To identify the levels of knowledge, attitudes, and behaviors related to monkeypox among men who have sex with men (MSM) in Kendari City in 2024. Method: The method used in this study was a quantitative descriptive approach with a cross-sectional design, involving 144 respondents who had undergone HIV screening at the Lepo-Lepo Health Center. Results: The results indicated that 83.3% of respondents had good knowledge, 74.3% demonstrated a positive attitude toward Mpox prevention, yet only 36.1% practiced preventive measures effectively. There remains a noticeable gap in the implementation of preventive actions despite adequate knowledge and attitudes. Respondents generally showed a positive perception of the importance of Mpox prevention; however, social stigma and limited access to information emerged as major challenges. Conclusion: This study concludes that community-based education and intervention programs are essential to improve preventive practices and to serve as a foundation for developing more effective health policies among high-risk populations.